Proteomics analysis reveals FEN1 as a promising therapeutic target against small cell neuroendocrine carcinoma of the cervix - Jianbing Liu; Meiying Zhong; Kai Yang; Jinjuan Wang; Haixia Ma; Wei Wang; Lin Sun; Lingling Liu; Jing Xu; Xiaohua Cui; Jianqing Hao; Li Li (Scientific Reports)
Abstract Small cell neuroendocrine carcinoma of the cervix (SCNECC) is a rare, aggressive cervical cancer with poor prognosis. This study explored molecular drivers of SCNECC progression and identified potential therapeutic targets. Proteomic analysis was conducted to identify differentially expressed proteins (DEPs) in SCNECC. Subsequent GO and KEGG enrichment analyses were performed to delineate key DEPs. Functional assays, including CCK-8, colony formation, cell cycle, and apoptosis assays, were conducted to assess the roles of target genes. Expression levels of target genes were validated using qRT-PCR, western blot, and immunohistochemistry (IHC). Proteomic profiling revealed 2333 DEPs in SCNECC, comprising 2168 upregulated and 165 downregulated proteins. GO and KEGG analyses revealed that the upregulated DEPs were predominantly enriched in processes occurring within the cell nucleus, such as DNA replication, reflecting heightened proliferative activity in SCNECC. IHC confirmed FEN1 overexpression. Functional assays showed that FEN1 knockdown suppressed cell viability, colony formation, and cell cycle, promoted apoptosis, and impeded tumor growth in mice. SC13, a FEN1 inhibitor, also had similar effects. Furthermore, silencing FEN1 markedly reduced PIK3CA, PCNA, and BCL-2 levels, while elevating Caspase-9 expression. CONCLUSION: FEN1 overexpression fuels SCNECC progression via PCNA regulation, positioning FEN1 as a promising SCNECC therapeutic target.